2017
DOI: 10.18632/oncotarget.22009
|View full text |Cite
|
Sign up to set email alerts
|

The WAVE3-YB1 interaction regulates cancer stem cells activity in breast cancer

Abstract: Resistance to therapy is the main cause of tumor recurrence and metastasis and cancer stem cells (CSCs) play a crucial role in this process, especially in triple-negative breast cancers (TNBCs). Unfortunately, no FDA-approved treatment is currently available for this subtype of BC, which explains the high rate of mortality in patients with TNBC tumors. WAVE3, a member of the WASP/WAVE actin-cytoskeleton remodeling family of protein, has been established as a major driver of tumor progression and metastasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 71 publications
2
70
0
Order By: Relevance
“…Disruption of WAVE3, a member of the WASP/WAVE actin-cytoskeleton remodeling family, substantially attenuated cancer stem cell (CSC) populations in TNBC cell lines through suppressing CSC self-renewal capacity and transcriptional regulation of CSC-specific genes. These results support the critical role of WAVE protein in TNBC chemoresistance [66]. CRISPRbased knockout of MAP3K1 in mutant PIK3CA breast cancer cell lines resulted in an increased proliferation rate and decreased sensitivity to an AKT inhibitor (AZD5363) through enhanced phosphorylation of AKT in vitro as well as in vivo [40].…”
Section: Breast Cancersupporting
confidence: 72%
“…Disruption of WAVE3, a member of the WASP/WAVE actin-cytoskeleton remodeling family, substantially attenuated cancer stem cell (CSC) populations in TNBC cell lines through suppressing CSC self-renewal capacity and transcriptional regulation of CSC-specific genes. These results support the critical role of WAVE protein in TNBC chemoresistance [66]. CRISPRbased knockout of MAP3K1 in mutant PIK3CA breast cancer cell lines resulted in an increased proliferation rate and decreased sensitivity to an AKT inhibitor (AZD5363) through enhanced phosphorylation of AKT in vitro as well as in vivo [40].…”
Section: Breast Cancersupporting
confidence: 72%
“…Because the results of in vitro analyses suggested that invasion abilities and CSC properties were suppressed by the overexpression of miR‐93, we used the TargetScan 6.2 algorithm (http://www.targetscan.org) to search for putative miR‐93 targets that play important roles in the regulation of CSC properties and cell invasion. The search identified the WASF3 ( WAVE3 ) gene as one of the promising candidates 28,29 . Importantly, WASF3 is an actin cytoskeleton remodeling protein, which often functions as an oncogene, and is established as a major driver of tumor progression, invasion (Figure and Table ), and metastasis of breast cancers, 9,29 and is a marker associated with worse patient prognosis 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, WASF3 is an actin cytoskeleton remodeling protein, which often functions as an oncogene, and is established as a major driver of tumor progression, invasion (Figure and Table ), and metastasis of breast cancers, 9,29 and is a marker associated with worse patient prognosis 29,30 . In addition, WASF3 promotes tumor sphere formation and the expression of CSC‐related genes 28 . Within its 3′‐UTR, WASF3 carries 2 predicted 8‐mer miR‐93 target sites (2728‐2735 and 3889‐3896 of the ): the former is poorly conserved across mammalian species, and the latter is highly conserved across mammalian species (Figure 4A, 8mer in lower boxes).…”
Section: Resultsmentioning
confidence: 99%
“…By systematically analyzing oncogenic signaling, we demonstrated that concurrent expression of oncogenic MET and PIK3CA synergistically activates multiple oncogenic signals, including RAS-MEK-MAPK, STAT3, and PI3K-AKT pathways in an HGF-enriched environment, and further markedly increases activation of Y-box binding protein 1 (YB1) that induces progression and metastasis of different types of cancer through angiogenesis, resistance of cell death, tumor-promoting inflammation, and evasion of immune destruction (40)(41)(42). Targeting PI3K significantly inhibits the PI3K-AKT pathway, whereas targeting MET dramatically inhibits the MAPK pathway and also inhibits the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%